Genotype and phenotype correlations in 441 patients with epidermolysis bullosa from China. (5th November 2022) - Chen, Fuying; Wei, Ruoqu; Deng, Dan; Zhang, Xue; Cao, Yu; Pan, Chaolan; Wang, Yumeng; Cao, Qiaoyu; Wang, Jianbo; Zeng, Ming; Huang, Linting; Gu, Yan; et al.
Abstract: Background: Epidermolysis bullosa (EB) is a heterogeneous group of rare and incurable genetic blistering disorders. Objectives: The objective was to analyse the genotype–phenotype correlation in EB among Chinese individuals. Methods: Next‐generation sequencing and Sanger sequencing were performed to genetically confirm clinically diagnosed EB. Reverse transcription‐PCR and splice‐site analysis were used to evaluate the consequences of splicing mutations. Results: A total of 441 cases (413 families) across 11 genes were included. EB simplex (EBS), junctional EB (JEB), dystrophic EB (DEB), Kindler EB, simplex and junctional compound EB accounted for 23.4%, 12.7%, 61.5%, 1.1% and 0.2%, respectively. In 16 probands with presumptive recessive EB, failed to find the second allele, COL7A1 (10), COL17A1 (4), LAMB3 (1) and ITGB4 (1). De novo mutations are common in dominant EB (63.8% in EBS, 27.5% in DEB) but extremely rare in recessive DEB (RDEB; 0.74%). Mosaicism is more common than presumed, with 5.4% of dominant EBS. In JEB, only 45.0% of patients with biallelic premature termination codon (PTC) mutations in laminin 332 genes died within 24 months, with a longer average survival age of 11.1 months. In JEB, unusual phenotypes are frequently observed, notably urinary tract involvement, duodenal atresia and EB nevi. In RDEB, 48.8% of cases with biallelic PTC mutations in COL7A1 exhibited a relatively mild phenotype; they are likely to develop a severe phenotype at 0–4 years old, and the PTC mutations position closer to the N‐terminal, leading to earlier onset. Glycine substitution mutations in DEB have complex genotypic and phenotypic heterogeneity. The rare subtype, dominant and recessive compound DEB, consists of 1.8% of the total DEB. Conclusions: This study reveals the general rules governing genotype–phenotype correlations, rare phenotypes and complex genotypes. Collectively, mutation analysis in different forms of EB provides the basis for improved subclassification with accurate genetic counselling and for prenatal diagnosis.